IMF Staff papers : Volume 39 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1992)
This paper examines market liberalization policies in a reforming socialist economy. The aim of this paper is to develop a model of such a reforming socialist economy and to explore the consequences of market-oriented policies in the context of such an economy. A model of a socialist economy is presented, incorporating bargaining over wages and employment in the socialized sector and shortages that are reflected in the black market. The model is used to analyze the implications of liberalization policies, including trade liberalization, an administered price increase, and provisions allowing for increased direct foreign investment. The nonsocialized sector is perfectly competitive and produces an output that is different from that of the socialized sector. It has a neoclassical production function using a sector-specific input (say, capital) and labor. The results suggest that reforms may have different effects under different trade regimes and that small price reforms may have perverse effects.